The relationship of indoxyl sulfate and p-cresyl sulfate with target cardiovascular proteins in hemodialysis patients - Ping-Hsun Wu; Yi-Ting Lin; Yi-Wen Chiu; Gabriel Baldanzi; Jiun-Chi Huang; Shih-Shin Liang; Su-Chu Lee; Szu-Chia Chen; Ya-Ling Hsu; Mei-Chuan Kuo; Shang-Jyh Hwang (Scientific Reports, 2021)
Abstract Protein-bound uremic toxins (Indoxyl sulfate [IS] and p-cresyl sulfate [PCS]) are both associated with cardiovascular (CV) and all-cause mortality in subjects with chronic kidney disease (CKD). Possible mechanisms have not been elucidated. In hemodialysis patients, we investigated the relationship between the free form of IS and PCS and 181 CV-related proteins. First, IS or PCS concentrations were checked, and high levels were associated with an increased risk of acute coronary syndrome (ACS) in 333 stable HD patients. CV proteins were further quantified by a proximity extension assay. We examined associations between the free form protein-bound uremic toxins and the quantified proteins with correction for multiple testing in the discovery process. In the second step, the independent association was evaluated by multivariable-adjusted models. We rank the CV proteins related to protein-bound uremic toxins by bootstrapped confidence intervals and ascending p-value. Six proteins (signaling lymphocytic activation molecule family member 5, complement component C1q receptor, C–C motif chemokine 15 [CCL15], bleomycin hydrolase, perlecan, and cluster of differentiation 166 antigen) were negatively associated with IS. Fibroblast growth factor 23 [FGF23] was the only CV protein positively associated with IS. Three proteins (complement component C1q receptor, CCL15, and interleukin-1 receptor-like 2) were negatively associated with PCS. Similar findings were obtained after adjusting for classical CV risk factors. However, only higher levels of FGF23 was related to increased risk of ACS. In conclusion, IS and PCS were associated with several CV-related proteins involved in endothelial barrier function, complement system, cell adhesion, phosphate homeostasis, and inflammation. Multiplex proteomics seems to be a promising way to discover novel pathophysiology of the uremic toxin.